A multispecies consortium of bacteria having plant growth promotion and antifungal activities, for the management of Fusarium wilt complex disease in potato (Solanum tuberosum L.). (October 2018) - Devi, Angom Romita; Sharma, Gauri Dutta; Majumdar, Pranab Bihari; Pandey, Piyush
Abstract: Fusarium oxysporum F9 and Fusarium sp. F15 were found to be the causal organisms of wilt disease complex of potato ( Solanum tuberosum L.) in Cachar region of Assam, India. Based on the biocontrol activity against the two fusaria and plant growth promoting attributes such as siderophore, IAA, HCN and chitinolytic activities, six bacterial isolates were selected. These isolates were identified as Pseudomonas aeruginosa (B4, B23, B25 and B35), Serratia marcescens (B8) and Alcaligenes feacalis (B16) based on their 16S rDNA homology. Further, BOX-PCR was used to evaluate genetic diversity among the isolates. The maximum inhibition of mycelial growth against F15 and F9, was shown by P. aeruginosa B35 (i.e. 76.15% and 85.88% respectively). All the isolates were found to produce IAA and siderophore. Three isolates, S. marcescens B8, P. aeruginosa B4, and P. aeruginosa B35 produced chitinase, and highest chitinase activity was recorded for B35 (0.70 U/ml). The genes for antibiotic synthesis such as phlD for 2, 4-diacetylphloroglucinol (DAPG) was present in A. feacalis B16, while phenazine ( phzF ) was found to present in all four pseudomonads (B4, B23, B25 and B35), which was confirmed by thin layer chromatography analysis. The inoculation of the bacterial consortium in fusaria infested soil (F9 + F15) resulted in a 94% reduction of wilt incidence, while plant biomass was also enhanced significantly (p < 0.05), as 186.9% increase in fresh weight and 214.75% increase in dry weight which was indicative of plant-probiotic effect of consortium, in addition to its biocontrol potential against Fusarium wilt in pot trial.